2012
DOI: 10.1002/chem.201102207
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Hydrophosphonylation of Aldehydes and Unactivated Ketones Catalyzed by Methylene‐Linked Pyrrolyl Rare Earth Metal Amido Complexes

Abstract: A series of rare earth metal amido complexes bearing methylene-linked pyrrolyl-amido ligands were prepared through silylamine elimination reactions and displayed high catalytic activities in hydrophosphonylations of aldehydes and unactivated ketones under solvent-free conditions for liquid substrates. Treatment of [(Me(3)Si)(2)N](3)Ln(μ-Cl)Li(THF)(3) with 2-(2,6-Me(2)C(6)H(3)NHCH(2))C(4)H(3)NH (1, 1 equiv) in toluene afforded the corresponding trivalent rare earth metal amides of formula {(μ-η(5):η(1)):η(1)-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 72 publications
1
15
0
Order By: Relevance
“…It is worth mentioning that starting from ketones, the accomplishment of the reaction is more challenging than in the cases applying aldehydes. The synthesis of α-alkyl-α-hydroxyphosphonates often requires the use of “exotic” catalysts [ 16 , 17 , 18 , 19 , 20 ], or an excess of a base. Procedures also applicable for the conversion of ketones are marked by an asterisk in Table 1 .…”
Section: Synthetic Routes Towards α-Hydroxyphosphonatesmentioning
confidence: 99%
“…It is worth mentioning that starting from ketones, the accomplishment of the reaction is more challenging than in the cases applying aldehydes. The synthesis of α-alkyl-α-hydroxyphosphonates often requires the use of “exotic” catalysts [ 16 , 17 , 18 , 19 , 20 ], or an excess of a base. Procedures also applicable for the conversion of ketones are marked by an asterisk in Table 1 .…”
Section: Synthetic Routes Towards α-Hydroxyphosphonatesmentioning
confidence: 99%
“…79 In a recent communication, Zhou and co-workers reported on synthesis of a series of dinuclear rare earth metal (i.e., yttrium, niobium, samarium, desprosium and ytterbium) amido complexes containing methylene-linked pyrrolylamido ligands and their application in the hydrophosphonylation of aldehydes and unactivated ketones, also under solvent-free conditions. 80 During preliminary experiments, the authors discovered that the reaction of benzaldehyde with diethylphosphite under neat conditions in the presence of 0.1 mol% of 12, a samarium amido complex containing a methylene-linked pyrrolyl-amido ligand, led to the desired α-hydroxyphosphonate in almost quantitative yield in only five minutes at room temperature. In an examination of the protocol's scope, it was shown that both aromatic and aliphatic aldehydes reacted well under solvent-free conditions at room temperature, yielding the desired α-hydroxyphosphonates in good to excellent yields in a reaction time of just five minutes (Table 35).…”
Section: Reactions Under Solvent-free Conditionsmentioning
confidence: 99%
“…This catalytic system was developed further by combining it with calix [4]pyrrole [61] to form dinuclear trivalent lanthanide amido complexes bearing tetra-anion calix [4]pyrrolyl ligands. Alternatively, the lanthanide catalyst could be combined with methylenelinked pyrrolyl-amino ligands [62] to form dinuclear lanthanide complexes. Both groups of catalysts turned out to be highly efficient for the hydrophosphonylation of aldehydes and inactivated ketones.…”
Section: Synthesis Of α-Hydroxyphosphonates and Related Compoundsmentioning
confidence: 99%